PORTALBIN sebagai inovasi platform pengelolaan sampah rumah tangga berbasis Ecopreneur digital bagi masyarakat Desa Wadung, Pakisaji, Malang - Anjar Nur Ramadhani; Ade Siyanti Nurul Hidayah; Yoyok Adisetio Laksono (Unri Conference Series: Community Engagement, 2021)
Household waste is waste that comes from daily activities in the household which does not include feces and specific waste. Improper waste management can have a negative impact on the surrounding environment. Based on the complaints of the people of RT 09 RW 03 in Wadung Village, waste processing in the area is considered not to be carried out comprehensively and caused a negative impact, such as air pollution which also affect the level of public health. Wadung Village needs digital media to improve skills in waste management. A simple media website, which is able to provide education about waste and the use of high-value products is expected to be able to provide solutions for the local community. Through the Community Service Student Creativity Program, we have a solution called "Innovation of Ecopreneur-Based Household Waste Management Platform for the Community of Wadung Village, Pakisaji Malang". This concept uses the blended learning method, which combines teaching with face-to-face and online. In addition, this concept combines three important components in sustainable development, namely environmental, economic and social care. When solution implemented, the public has understood the importance of waste management, the implementation of digital ecopreneurs, and the utilization of the PORTALBIN platform.